Internationalisation Strategy and Management Accounting and Control Systems: A Network Approach - Ana Filipa M. Roque; Maria-Céu G. Alves; Mário Lino Raposo (Asian Academy of Management Journal of Accounting and Finance, 2024)
Internationalisation has become crucial to economic development, especially for companies that are more technological and scientific. These companies arouse curiosity, as they quickly begin their internationalisation process (IP), adopting the Born Global model shortly after its creation. It has also been noted that, when they seek to benefit from mutual flexibility, the opportunity to use technical and economic knowledge, and even the collective assumption of costs and risks, it is common for them to resort to the internationalisation model based on Network Theory. Considering that internationalisation is part of the company’s growth strategy, and that this may require an adjustment of the information structure, namely the Management Accounting and Control System (MACS), it becomes relevant to understand how IP affects MACS. In this way, our study aims to respond to how MACS adjusts to Born Global internationalisation model (BGIM) and Network Model of Internationalisation (NMI) for a successful internationalisation strategy? In this study, we evaluate how MACS is adjusted in order to become a tool capable of collecting and processing the set of useful information necessary for the implementation of the internationalisation strategy. We conducted a single case study in a Portuguese health-sector company. Our results show that MACS needs to be adjusted to facilitate the implementation of IP.